Wind-induced responses of a tall building with a double-skin façade system. Issue 168 (September 2017) - Hu, Gang; Hassanli, Sina; Kwok, K.C.S.; Tse, K.T.
Abstract: To date the engineering community has seen double-skin façade systems as non-structural elements on buildings for the aesthetic desire, improving the indoor environment, reducing the energy use, and even improving acoustics in buildings. In this study, the effects of a double-skin façade system on the wind-induced responses of a tall building were investigated via a program of wind tunnel tests. Two types of wind tunnel tests, i.e. aeroelastic test and pressure test, were performed. It was found that a double-skin façade with/without vertical openings installed in front of the windward face of the building model results in very different effects on the wind-induced responses in alongwind and crosswind directions. In the alongwind direction, the façade with/without openings induces negligible effects on the wind-induced response. However, in the crosswind direction, the façade with opening(s) reduces the wind-induced response significantly, whereas the façade without any opening increases the response, compared to the bare tall building model. Therefore, in addition to achieve the purposes of the aesthetic desire, improving indoor environment and reducing energy use, the double-skin façade system with vertical opening(s) can also be used to effectively reduce crosswind responses without inducing larger alongwind responses. Highlights: Façade induces different effects on responses in alongwind and crosswind directions. Façade with or without openings induces negligible effects on alongwind response. Façade with opening(s) reduces the crosswind response significantly. Façade without any opening increases the crosswind response.